A SIMPLE CALCULATION OF GRAVITATIONAL LENSING ON THE ROTATING STARS - Norma Sidik Risdianto; Agung Laksana; Asih Melati (Integrated Lab Journal, 2018)
We propose a simple calculation to obtain the gravitational lensing on rotating stars. The calculation has been made by using a Lagrangian of Kerr metric and getting  for deflection angle. The calculation has been reduced to slow-rotating stars and equatorials case ()  for maximum deflection angle.